Angiotensin-converting Enzyme/Vitamin D receptor gene polymorphisms and bioelectrical impedance analysis in predicting athletic performances of Italian young soccer players - Micheli, M. L.; Gulisano, M.; Morucci, G.; Punzi, T.; Ruggiero, M.; Ceroti, M.; Marella, M.; Castellini, E.; Pacini, S. (The Journal of Strength and Conditioning Research, 2011)
We evaluated the association between 2 genetic polymorphisms known to be involved in fitness and performance, and anthropometric features, body composition, and athletic performances in young male soccer players with the goal of identifying genetic profiles that can be used to achieve maximal results from training. One hundred twenty-five medium-high-level male soccer players were genotyped for angiotensin-converting enzyme (ACE) I/D, and vitamin D receptor (VDR) FokI gene polymorphisms and scored for anthropometric measurements, body composition, and athletic performance. Body mass index, fat mass, fat-free mass, resistance, reactance, impedance, phase angle (PA), and body cell mass were measured. Athletic performance was evaluated by squat jump, countermovement jump (CMJ), 2-kg medicine ball throw, 10- and 20-m sprint time. We observed that the homozygous ff genotype of the VDR gene was significantly more represented in young soccer players than in a matched sedentary population. Values of reactance and PA were differently distributed in ACE and VDR genotypes with high mean values in subjects with DD (ACE) and FF (VDR) genotypes. No correlation was observed between ACE or VDR genotypes and 2-kg medicine ball throw, 10- and 20-m sprint times. The ID genotype of ACE was associated with the best performances in squat jump and CMJ. Our results suggest that determination of ACE and VDR genotypes might help select those young athletes harboring the most favorable genetic potential to succeed in soccer.